(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
Discrimination remains a pervasive issue in societies worldwide, affecting individuals based on race, gender, religion, disability, and other factors. Educating children about discrimination is essential in fostering empathy, inclusivity, and social harmony. This study explores various approaches to teaching children how to recognize and challenge discrimination.